Quality of Life and Surgical Outcome After Total Laparoscopic Hysterectomy Versus Total Abdominal Hysterectomy for Benign Disease: A Randomized Controlled Trial - Chaitra R P; Mahendra G; Shruti K K; Yanamadala Lijaswi (Public Health, 2026)
Hysterectomy is a widely performed surgical procedure for benign gynecological conditions such as uterine fibroids, abnormal uterine bleeding, and endometriosis. This randomized controlled trial compares total laparoscopic hysterectomy (TLH) and total abdominal hysterectomy (TAH) in terms of surgical outcomes and quality of life (QoL). Sixty participants were randomized into two groups: TLH (n=30) and TAH (n=30). TLH demonstrated reduced blood loss, shorter hospital stays, and higher QoL scores on the RAND-36 questionnaire compared to TAH, despite longer operating times. These findings reinforce TLH as the preferred approach for managing benign gynecological conditions.